Translation Techniques in the Comic "Pyramid Game" - Ahmadi, Anggun Farida; Darmawan, I Nyoman Pasek; Samosir, Sahat Maringan (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2024)
This study examined the translation techniques used in the comic Pyramid Game from English to Bahasa Indonesia. As digital media continues to evolve, digital comics have become an increasingly valuable medium for fostering reading interest and promoting literacy. This study employed a qualitative method to analyze the translation of 15 English sentences from the digital comic into Bahasa Indonesia, selecting sentences from Part 1 to Part 10 based on their linguistic complexity and relevance to the Indonesian context and culture. The findings identified various translation techniques, highlighting their importance in conveying meaning while addressing cultural and linguistic nuances. The study also illustrates how different translation techniques were chosen and applied based on the context of each sentence. This research provides valuable insights for students at Universitas Terbuka and other interested readers, particularly in the field of translation studies, by exploring the diverse strategies applied in translating various materials.